The Importance of Teacher's Pedagogic Competence in Islamic Religious Education - Rohana, Syarifah (Darul Ilmi Bina Insan Foundation, 2023)
This paper examines the importance of the pedagogic competence of Islamic religious education (IRE) teachers. The expertise of a teacher in mastering pedagogical competencies is highly expected. An IRE teacher who has pedagogic competence if he is able to know the characteristics of students, because in this competency is expressed and implied a knowledge that learns about how to educate, guide students according to their development. A teacher is also required to be skilled in interacting with his students, as well as skilled in managing the learning process in the classroom. Through pedagogic competence it can be seen to what extent he has mastered the four teacher competencies, one of which is pedagogic competence. This competence will distinguish the teaching profession from other professions . In this way, if the IRE teacher is able to understand each student's characteristics, then the learning process will be more effective and efficient , and can overcome the problems that occur in students in the classroom.